One parameter family of b-m1 developable surfaces of biharmonic new type b-slant helices according to Bishop frame in the sol space sol 3 - Ergüt, Mahmut; Körpinar, Talat; Turhan, Essin (My University, 2013)
In this paper, we study inextensible flows of b-m1 developable surfaces of biharmonic new type b-slant helix in the Sol3. We characterize one parameter family of the b-m1 developable surfaces in terms of their Bishop curvatures. © SPM.
Keywords: B-m1 developable; Curvatures; New type b-slant helix; Sol space